Sodium Chloride and Water Transport in the Medullary Thick Ascending Limb of Henle. EVIDENCE FOR ACTIVE CHLORIDE TRANSPORT - Rocha, Antonino S.; Kokko, Juha P. (The Journal of Clinical Investigation, 1973)
Transport of NaCl and water was examined in the rabbit medullary thick ascending limb of Henle (ALH) by perfusing isolated segments of these nephrons in vitro. Osmotic water permeability was evaluated by perfusing tubules against imposed osmotic gradients. In these experiments the net transport of fluid remained at zero when segments of thick ALH were perfused with isotonic ultrafiltrate in a bath of rabbit serum in which the serum osmolality was increased by the addition of either 239±8 mosmol/liter of raffinose or 232±17 mosmol of NaCl indicating that the thick ascending limb of Henle is impermeant to osmotic flow of water. When these tubules were perfused at slow rates with isosmolal ultrafiltrate of same rabbit serum as used for the bath, the effluent osmolality was consistently lowered to concentrations less than the perfusate and the bath. That this decrease in collected fluid osmolality represented salt transport was demonstrated in a separate set of experiments in which it was shown that the sodium and chloride concentrations decreased to 0.79±0.02 and 0.77±0.02 respectively when compared with the perfusion fluid concentrations. In each instance the simultaneously determined transtubular potential difference (PD) revealed the lumen to be positive with the magnitude dependent on the perfusion rate. At flow rates above 2 nl·min-1, the mean transtubular PD was stable and equal to 6.70±0.34 mv. At stop-flow conditions this PD became more positive. Ouabain and cooling reversibly decreased the magnitude of this PD. The transtubular PD remained positive, 3.3±0.2 mV, when complete substitution of Na by choline was carried out in both the perfusion fluid and the bathing media. These results are interpreted to indicate that the active transport process is primarily an electrogenic chloride mechanism. The isotopic permeability coefficient for Na was 6.27±0.38 × 10-5 cm·s-1 indicating that the thick ALH is approximately as permeable to Na as the proximal convoluted tubule. The chloride permeability coefficient for the thick ALH was 1.06±0.12 × 10-5 cm·s-1 which is significantly less than the chloride permeability of the proximal tubule. These data demonstrate that the medullary thick ascending limb of Henle is water impermeable while having the capacity for active outward solute transport as a consequence of an electrogenic chloride pump. The combination of these characteristics allows this segment to generate a dilute tubular fluid and participate as the principal energy source for the overall operation of the countercurrent multiplication system. Images